GASKET SOLUTIONS FOR ELECTROLYZERS – AN OVERVIEW - Hickmann, Thorsten (International Journal of Research -GRANTHAALAYAH, 2023)
Electrolysis seals play an important role in the chemical industry and are used to seal liquids and gases in electrolysis cells. A good seal is critical to the performance and reliability of the electrolysis process, ensuring that no unwanted substances enter the system and that the correct amount of liquid and gas flows through the cell. This article explains the most important aspects of seal geometries, materials for electrolytic seals and required equipment.